2021
DOI: 10.1021/acsaem.1c01169
|View full text |Cite
|
Sign up to set email alerts
|

Quinolinediol Molecule Electrode and MXene for Asymmetric Supercapacitors with Efficient Energy Storage

Abstract: Asymmetric supercapacitors (ASCs) need positive and negative electrodes to produce a larger redox peak position difference to achieve a higher energy density. Here, 2,8-quinolinediol (QD) is adopted to modify reduced graphene oxide (rGO) and prepare an organic molecule electrode (OME), in which the Faraday reaction occurs in a more positive potential range. The electrochemical tests show that the optimized OME (QD/rGO-0.75) releases a high special capacitance (371 F g–1 at 5 mV s–1) and exhibits an excellent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 53 publications
(76 reference statements)
1
27
0
Order By: Relevance
“…In addition, Ti 3 C 2 T x (MXene) has excellent electrical conductivity, abundant surface groups, pseudocapacitance characteristics, and good cyclic stability. , Therefore, Ti 3 C 2 T x (MXene) has attracted the attention of researchers. For instance, Jiao et al synthesized 2,8-quinolinediol@rGO//Ti 3 C 2 T x . The device showed an energy density of 27.8 W h kg –1 in an operating voltage of 0–1.6 V. Boota et al assembled a 2,5-dihydroxy-1,4-benzoquinone@rGO//Ti 3 C 2 T x SC, which indicated an operating voltage of 0–1.4 V and an energy density of 40 W h kg –1 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Ti 3 C 2 T x (MXene) has excellent electrical conductivity, abundant surface groups, pseudocapacitance characteristics, and good cyclic stability. , Therefore, Ti 3 C 2 T x (MXene) has attracted the attention of researchers. For instance, Jiao et al synthesized 2,8-quinolinediol@rGO//Ti 3 C 2 T x . The device showed an energy density of 27.8 W h kg –1 in an operating voltage of 0–1.6 V. Boota et al assembled a 2,5-dihydroxy-1,4-benzoquinone@rGO//Ti 3 C 2 T x SC, which indicated an operating voltage of 0–1.4 V and an energy density of 40 W h kg –1 .…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that some of the peaks of the PGF are shifted to lower energies due to interactions between rGO and PPy. 35,38 Based on the above results, we believe that the nanostructured composite is indeed composed of PPy and graphene. Thermal stability testing was carried out using thermogravimetric analysis (TGA).…”
Section: Resultsmentioning
confidence: 70%
“…It can be seen that peaks at 3398, 1395 and 1114 cm −1 can be attributed to the –OH stretching vibration, the bending vibration of –OH on the aromatic ring, and O–C–O stretching of the rGO film, respectively. 35 For PPy, the absorption peaks at 3420, 1537 and 1142 cm −1 are assigned to the N–H vibrations, skeletal vibrations of the pyrrole ring, and C–N stretching vibrations. 36 Peaks at 1036 and 872 cm −1 are assigned to C–H deformation vibrations.…”
Section: Resultsmentioning
confidence: 99%
“…For single GO dispersion, re-aggregation, and stacking between GO sheets, the addition of HAQ can not only alleviate the re-accumulation of GO nanosheets but also generate abundant new pores, providing a shortcut for the diffusion of electrolyte ions and finally form a new three-dimensional hierarchical pore structure of the hydrogel composite electrode material. , During the reaction, GO is converted into conductive rGO, and HAQ is adsorbed on rGO via π–π superposition, noting that HAQ plays a crucial role in the recovery of the π-conjugated system in defective GO nanosheets …”
Section: Resultsmentioning
confidence: 99%
“…HAQ-rGO(0.5:1) exhibits interconnected 3D hierarchical porous characteristics, and the pore size varies from sub-micrometers to several micrometers. This thin porous wall and open network can be thought of as an ion-buffering reservoir, shortening the distance between the ions of the electrolyte diffusing to the graphene thin films and facilitating rapid ion transport . The detailed structures of rGO and HAQ-rGO(0.5:1) were further observed by TEM analysis.…”
Section: Resultsmentioning
confidence: 99%